Understanding Classroom Activities in Speaking Courses in College: A Case Study in the Post-Pandemic Era - Ulayya, Nadiya Kaltsum; Anggraini, Hesti Wahyuni (Utamax : Journal of Ultimate Research and Trends in Education, 2024)
Classroom activities are crucial in speaking courses as they significantly influence students' speaking abilities. It is imperative for lecturers to employ appropriate activities tailored to student needs. This study aims to investigate the classroom activities utilized by a lecturer in a "Speaking for Informal Interaction" class for first-semester students at the English Education Study Program of Sriwijaya University. This qualitative case study investigated the classroom activities employed by a lecturer in the "Speaking for Informal Interaction" class for first-semester students at the English Education Study Program of Sriwijaya University. Purposive sampling was utilized to select a sample comprising one lecturer and six students out of a total of thirty-three. Data collection methods included document analysis, observation, and interviews, followed by a three-step qualitative data analysis process: data reduction, data display, and conclusion drawing. The investigation revealed a variety of classroom activities structured into three stages, including 10 activities during the "whilst activities" phase: prepared talk, discussion, role-play, storytelling, brainstorming, interviews, describing pictures, reporting, communication games, and question and answer sessions. These activities were found to significantly enhance student engagement and comprehension in the speaking class. These results underscore the importance of varied and interactive classroom activities in language education, potentially informing curriculum design and teaching strategies not only in English education but also in language learning contexts worldwide. By embracing diverse pedagogical techniques, educators can better cater to students' learning needs, ultimately contributing to more effective and engaging language education globally.